2017
DOI: 10.1590/0037-8682-0002-2017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for multidrug-resistant tuberculosis in Iran and its neighboring countries: systematic review and meta-analysis

Abstract: Tuberculosis, in particular drug-resistant tuberculosis, is of global concern due to the high mortality and morbidity associated with it annually. The aim of this study was to determine the prevalence of and the risk factors for multidrug-resistant tuberculosis in Iran and its neighboring countries. Four databases (PubMed, BioMed Central, EMBASE, and Web of Science) were searched using key terms. Nineteen eligible articles were identified, of which 12 and seven were used for quantitative and qualitative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
(47 reference statements)
3
16
1
1
Order By: Relevance
“…And previous treatment was a major predictor of MDR-TB in this study. Similar ndings were found in a number of studies from different countries including the Ethiopia, East Shoa(11), Amhara regional state(32), Addis Ababa(10), Iran and neighboring countries (38),Iran (27),Nepal (39),China(26),Sub-Saharan countries review(9), retrospective study in Nigeria(40), Equatorial Guinea(34), Tanzania(33), USA(4). Systematic review and meta-analysis in Ethiopia(12) revealed previous treatment was a major determinant of MDR-TB, systematic review in Europe (41).…”
Section: Discussionsupporting
confidence: 78%
“…And previous treatment was a major predictor of MDR-TB in this study. Similar ndings were found in a number of studies from different countries including the Ethiopia, East Shoa(11), Amhara regional state(32), Addis Ababa(10), Iran and neighboring countries (38),Iran (27),Nepal (39),China(26),Sub-Saharan countries review(9), retrospective study in Nigeria(40), Equatorial Guinea(34), Tanzania(33), USA(4). Systematic review and meta-analysis in Ethiopia(12) revealed previous treatment was a major determinant of MDR-TB, systematic review in Europe (41).…”
Section: Discussionsupporting
confidence: 78%
“…There are different factors affecting the incidence of TB in various areas, such as weather, epidemiological transition, drug resistance, HIV, migration, and poverty. These factors might increase the incidence of TB (5,6,15).…”
Section: Discussionmentioning
confidence: 99%
“…During two decades, the TB incidence rate in Iran declined from 36 per 100000 in 1990 to 17 per 100000 in 2010, but it is not enough to reach the STB goal; hence, TB control is a prime concern for public health among policymakers. One of the important causes of this situation is the common frontier with three countries in which TB is a public health problem, i.e., Pakistan, Iraq, and Afghanistan (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and foreign research reports indicated MDR-TB was closely related to a number of factors such as sociodemographic factors, economic level, and past anti-TB treatment courses, [4][5][6][7][8][9][10][11][12][13][14] and these factors may differ by region or country. MDR-TB risk factors were not yet determined in Anhui province.…”
mentioning
confidence: 99%